2017
DOI: 10.3892/mco.2017.1511
|View full text |Cite
|
Sign up to set email alerts
|

Significance of lung biopsy for the definitive diagnosis of lung nodules in breast cancer patients

Abstract: The aim of the present study was to evaluate the significance of lung biopsy for the modification of the treatment strategy in breast cancer patients who develop lung nodules during follow-up after breast surgery. Of 53 consecutive patients who underwent lung biopsies in two institutions (Hiroshima University Hospital and Hiroshima Prefectural Hospital, Hiroshima, Japan) between 1997 and 2014, 45 underwent lung surgery and 8 underwent percutaneous or transbronchial tumor biopsy for lung nodules developing afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
1
0
2
Order By: Relevance
“…Matsuura et al showed in a sample of 53 patients with breast cancer and suspected pulmonary metastases that 47% had confirmed pulmonary metastases, 40% had a second primary (primary malignant lung cancer), and 13% had benign disease. 30 Caparica et al, evaluated biopsies of pulmonary nodules in 228 patients with non-pulmonary cancer and showed that metastases were found in 64%, a secondary primary malignancy (lung cancer) in 26.3%, and 9.6% had benign disease. 31 The data suggest that assuming a pulmonary nodule is actionable at 8 mm, and assuming the previous CT had a nodule at least 2 mm in size (approximately the lower limits of detection by CT), then in 252 days (approximately 8.4 months; 95% CI (4.9, 10.2) months), an untreated nodule is expected to grow by 6 mm, from 2 to 8 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Matsuura et al showed in a sample of 53 patients with breast cancer and suspected pulmonary metastases that 47% had confirmed pulmonary metastases, 40% had a second primary (primary malignant lung cancer), and 13% had benign disease. 30 Caparica et al, evaluated biopsies of pulmonary nodules in 228 patients with non-pulmonary cancer and showed that metastases were found in 64%, a secondary primary malignancy (lung cancer) in 26.3%, and 9.6% had benign disease. 31 The data suggest that assuming a pulmonary nodule is actionable at 8 mm, and assuming the previous CT had a nodule at least 2 mm in size (approximately the lower limits of detection by CT), then in 252 days (approximately 8.4 months; 95% CI (4.9, 10.2) months), an untreated nodule is expected to grow by 6 mm, from 2 to 8 mm.…”
Section: Discussionmentioning
confidence: 99%
“…El pulmón es uno de los principales sitios de metástasis de cáncer de mama, especialmente en los tumores triple negativos, a diferencia de los tumores luminales donde el sitio más común son los huesos (3). La presencia de nódulos pulmonares en imágenes diagnósticas de estadificación o seguimiento son muy frecuentes en pacientes con cáncer y de ahí la importancia de su confirmación histopatológica por la posibilidad de encontrar otras etiologías como: segundos tumores primarios pulmonares, metástasis de otros órganos, tumores pulmonares benignos, infecciones, vasculitis o secundarios a enfermedades exposicionales (4)(5)(6)(7).…”
Section: Introductionunclassified
“…Es importante aclarar la etiología de los nódulos pulmonares en las pacientes con cáncer de mama ya que su etiología determina el abordaje terapéutico (8). El diagnóstico de enfermedad metastásica por cáncer de mama implica el uso de tratamientos sistémicos agresivos, con un impacto significativo en la supervivencia global que puede llegar a 12 o 24 meses en algunas series (6,9,10). A diferencia del diagnóstico de segundos tumores primarios pulmonares que requieren una estadificación y un manejo diferente dado que el tratamiento administrado con intención curativa puede lograr supervivencias por encima del 90% (11).…”
Section: Introductionunclassified